Relevan Mathematics Learning Models In Elementary School In The Era Of Industrial Revolution 4.0 - Pusparini, Dinar; Na’imah, Na’imah; Istiningsih, Istiningsih; Sih Dewanti, Sintha; Nazliati, Nazliati; Apliyanti, Selvy (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
This study was conducted to find a relevant learning model in mathematic lessons in Elementary School in the Industrial Revolution 4.0 era, which is marked by rapid technological advanced. Mathematic learning as an important foundation in understanding high-level technological concept, integrating technology into the mathematics curriculum addresses inequality of access to digital resources, and engaging students in more interactive and contextual mathematics learning. The method used in this study is a qualitative method with a case study method and literature review. The result of this study are by applying several learning models such as contextual learning models, STEAM and game-based learning models, students can develop critical thinking, problem solving, creative thinking, innovation, communication and collaborating.